1997
DOI: 10.1074/jbc.272.10.6105
|View full text |Cite
|
Sign up to set email alerts
|

Interactional Cloning of the 84-kDa Major Outer Dense Fiber Protein Odf84

Abstract: The study of mammalian sperm tail outer dense fibers (ODF), a structure of unknown function, is hampered by the insoluble nature of ODF proteins and the availability of only one cloned component, Odf27. We report here the first use of the Odf27 leucine zipper as bait in a yeast two-hybrid screen to isolate a novel testis-specific protein whose interaction with Odf27 depends critically on the Odf27 leucine zipper. We find that the novel gene, 111-450, encodes a product that localizes to ODF as determined by flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
118
1
7

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 94 publications
(129 citation statements)
references
References 58 publications
3
118
1
7
Order By: Relevance
“…These findings are in contrast with earlier studies of Odf2 expression, which identified it as being testis specific (Brohmann et al, 1997;Hoyer-Fender et al, 1998;Schalles et al, 1998;Shao et al, 1997;Turner et al, 1997). Odf2 was reportedly expressed specifically in male germ cells from the secondary spermatocyte stage onwards, with expression reaching its maximal level in the round spermatid (Horowitz et al, 2005;Hoyer-Fender et al, 1998;Turner et al, 1997).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…These findings are in contrast with earlier studies of Odf2 expression, which identified it as being testis specific (Brohmann et al, 1997;Hoyer-Fender et al, 1998;Schalles et al, 1998;Shao et al, 1997;Turner et al, 1997). Odf2 was reportedly expressed specifically in male germ cells from the secondary spermatocyte stage onwards, with expression reaching its maximal level in the round spermatid (Horowitz et al, 2005;Hoyer-Fender et al, 1998;Turner et al, 1997).…”
Section: Discussioncontrasting
confidence: 99%
“…As a result, details of the in vivo role of ODF2 in formation of the outer dense fibers and in its recently identified role at the centrosome have been lacking. Such a model would be invaluable in determining whether Odf2 is required specifically during spermatogenesis, as was originally suggested (Brohmann et al, 1997;Hoyer-Fender et al, 1998;Schalles et al, 1998;Shao et al, 1997;Turner et al, 1997), or whether Odf2 also plays key roles at the centrosome in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations